Eksperimen Pembelajaran Matematika dengan Strategi Numbered Head Together dan Group Investigation terhadap Hasil Belajar Siswa ditinjau dari Motivasi Belajar Pada Kelas VII SMP Negeri 2 Karangmalang Sragen Semester Genap Tahun 2016/2017 - Mustofa, Devi; , Drs. Slamet H.W,M.M, M.Pd (2017)
The purpose of the research are to analyze: (1) the effect of learning strategies Numbered Head Together and Group Investigation on learning outcomes. (2) the effect student learning motivation for learning ourcomes. (3) the teraction between learning strategy Numbered Head Together and Group Investigation terms of motivation on learning outcomes. Type of the research quantitative with quassi experimental esign. Sample were taken by Cluster random sampling of the pulation of all students of class VII SMP Negeri 2 Karangmalang demic year 2016/2017. Data collection techniques by using tionnaires, tests and documentation. Before to the analysis, first tested the normality and homogeneity test. The hypotesistent use unvalance two way analysis of variance with α=5% . the result of this study showed: (1) there was the effect of learning strategies Numbered Head Together and Group Investigation on learning outcones. (2) there was not effect student learning motivation for learning outcomes. (3) there was not interaction between the learning trategies Numbered Head Together and Group Investigation and motivation on learning outcomes.Keywords: learning outcomes, student learning motivation, Numbered Head Together, Group Investigation